Comparative review of business group affiliates and firms' performance: A meta-analysis research. Issue 4 (11th November 2019) - Lin, Chinho; Nguyen, Hoang Cong; Tran, Ha Hoang
Abstract : Purpose: The purpose of this paper is to synthesize empirical results relating to antecedents influencing differences in performance between business group (BG) affiliated firms and independent firms in emerging economies. Design/methodology/approach: A metanalysis was conducted in this research in which samples were collected, and a continuous data set for figuring the differentiation between group and non-group variables was selected and analyzed. These variables included performance, diversification, ownership characteristics, firm characteristics and group characteristics. Findings: The research presents a set of hypotheses from a model that shows the influences of factors moderating the differences between the performance of BG affiliates and independent firms, including governance and the kinds of strategic choices which these firms make. Four of the five hypotheses were totally supported, showing the importance of differentiating affiliates' and independent firms' performance in terms of ownership concentration, dividend payout, leverage, R&D, as well as diversification and a firm's age and size. Originality/value: The study focused its research on an examination of pyramid and cross-holding groups in order to reveal the role of the core firms. It also examines ownership concentration, as well as internal relationships with capital structure, and the effect which these have on firm performance, in order to further understand the relationship among BGs, corporate governance and performance in emerging-market economies.